Gaya Busana Sebagai Salah Satu Representasi Imperialisme Budaya Pada Film Bumi Manusia - Kristiawati, Erna; Purwanti, Angel (LPPM Universitas Putera Batam, 2022)
Bumi Manusia is a film that tells the love story of two characters named Minke and Annelies. The film, which premiered on the big screen on August 15, 2019, was realized in a colonial land setting in the early 20th century. The purpose of this research is to find out the representation of cultural imperialism in the film Bumi Manusia. This research is a descriptive qualitative research with the technique of observation, documentation and literature study. The results of this study show that fashion as a representation of cultural imperialism in the film Bumi Manusia is influenced by two cultures, namely European and Japanese cultures. Eropean fashion style is represented in three types, namely, daily fashion, pajamas and wedding clothes. Japanese fashion style is represented in the use of Kimono. Japanese fashion style is not dominant in the film.